A color vision approach considering weather conditions based on auto encoder techniques using deep neural networks - Raj, Mohammad Mainuddin; Tasdid, Samaul Haque; Nidra, Maliha Ahmed; Noor, Jobaer; Ria, Sanjana Amin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.